ChemInform Abstract: Atherton‐Todd Reaction: Mechanism, Scope and Applications. Issue 29 (July 2015) - Le Corre, Stephanie S.; Berchel, Mathieu; Couthon‐Gourves, Helene; Haelters, Jean‐Pierre; Jaffres, Paul‐Alain
Abstract Review: 146 refs.